Pemanfaatan Google Form: Inovasi Penilaian Sumatif Akhir Semester (SAS) Bidang Studi Bahasa Indonesia untuk Siswa Kelas 8 di SMP Negeri 37 Sinjai - Mustabsyirah, Mustabsyirah; Damopolii, Muljono; Yaumi, Muhammad (YASIN, 2025)
This research discusses the utilization of Google Form integrated with the belajar.id account in the implementation of the End of Semester Summative (SAS) in the Indonesian language subject for grade 8 students at SMP Negeri 37 Sinjai. This research focuses on the importance of assessment in the educational process, especially in measuring students' competency achievement efficiently and integrated with technology. The research method used was qualitative with semi-structured interviews with an Indonesian language teacher who has more than five years of experience. The results showed that Google Form offers a number of advantages, such as ease of use, randomization of questions, and automation of assessment, thus helping to speed up the evaluation process and minimize manual errors. However, technical issues such as unstable internet connection and limited question features were the main challenges. Teachers and students generally responded positively to the use of Google Forms, especially in terms of efficiency and ease of access. The implementation of Google Forms in SAS effectively increases the efficiency of assessment, although it requires better infrastructure support and training for users. Further development in platform features and improvement in digital literacy are needed to ensure the sustainability and effectiveness of Google Form use in the future.